Analisis Mendalam Perilaku Menyimpang White‑Collar Crime (Studi Kasus melalui Lensa Teori Convenience) - Rumahorbo, Liberti; Yusuf, Hudi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
White-collar crime is a form of nonviolent crime committed by individuals or groups with high social status, usually within a corporate or bureaucratic environment. These crimes are often difficult to detect and receive legal handling disproportionate to their harmful impact. This journal analyzes the phenomenon of white-collar crime through the convenience theory approach developed by Petter Gottschalk. This theory explains that white-collar crime arises from a combination between the motive, opportunity, and will of the perpetrator. The study used qualitative methods with literature study to analyze the causal factors and mechanisms of white-collar crime, as well as analyze some relevant case studies. The results of the analysis indicate that these crimes thrive in permissive systems, weak oversight, as well as organizational cultures that prioritize results without regard for integrity. Prevention strategies need to be thoroughly implemented through strengthening internal control systems, ethics education, legal reform, and building a transparent organizational culture. By understanding the roots of the problem through a theoretical lens, it is hoped that the tackling of white-collar crime can be more effective and equitable.